Determinants and processes of HIV status disclosure to HIV - infected children aged 4 to 17 years receiving HIV care services at Baylor College of Medicine Children’s Foundation Tanzania, Centre of Excellence (COE) in Mbeya: a cross-sectional study - Nzota, Mary S.; Matovu, Joseph K. B.; Draper, Heather R.; Kisa, Rose; Kiwanuka, Suzanne N. (BMC pediatrics, 2015)
Disclosure of HIV sero-status to HIV-infected children is associated with reduced risk of death and better adherence to antiretroviral drugs. However, caregivers find it difficult to determine when and how they should disclose the HIV sero-positive status to HIV-infected children. In this study, we assessed the determinants and processes of HIV status disclosure to HIV-infected children aged 4 to 17 years receiving HIV care services at the Baylor College of Medicine Children's Foundation Tanzania, Centre of Excellence (COE) in Mbeya. Methods: This was a cross-sectional study conducted among 334 caregivers of HIV positive children attending the Baylor COE in Mbeya, Tanzania. Data were collected using quantitative and qualitative research methods. Quantitative data were collected on socio-demographic characteristics of children and caregivers using an interviewer-administered questionnaire. Data were entered into Epi-Info version 3.5.1 and analyzed using STATA version10. Univariable and multivariable logistic regression analyses were conducted to obtain odds ratios (OR) and 95 % confidence intervals (95 % CI) associated with disclosing HIV positive status to HIV-infected children. Qualitative data were collected on the processes used in accomplishing the HIV status disclosure event using case histories and key informant interviews and analyzed manually using latent analysis techniques. Results: About one-third of the caregivers (32.6 %) disclosed the children’s HIV sero-positive status to them. Disclosure was more likely among children 10 years or older (adjusted OR [AOR] = 8.8; 95 % CI: 4.7, 16.5), caregivers with knowledge about HIV disclosure (AOR = 5.7; 95 % CI: 2.3, 13.7) and those earning more than Tsh 99,999 (US $62.5) per month (AOR = 2.4; 95 % CI: 1.3, 4.5). Qualitative findings showed that caregivers used a diversity of approaches to complete the HIV status disclosure event including direct, third-party, event-driven and use of drawings. Conclusions: Our study shows that disclosure is common among older children and is largely driven by the caregivers’ knowledge about HIV status disclosure and monthly earnings. HIV status disclosure was accomplished through a variety of approaches. These findings suggest a need to provide caregivers with knowledge about HIV status disclosure approaches to improve HIV status disclosure to HIV-infected children.
Keywords: Disclosure; HIV- infected children; Determinants; Processes